DNA damage triggers SAF-A and RNA biogenesis factors exclusion from chromatin coupled to R-loops removal. Issue 14 (10th August 2014) - Britton, Sébastien; Dernoncourt, Emma; Delteil, Christine; Froment, Carine; Schiltz, Odile; Salles, Bernard; Frit, Philippe; Calsou, Patrick
Abstract : We previously identified the heterogeneous ribonucleoprotein SAF-A/hnRNP U as a substrate for DNA-PK, a protein kinase involved in DNA damage response (DDR). Using laser micro-irradiation in human cells, we report here that SAF-A exhibits a two-phase dynamics at sites of DNA damage, with a rapid and transient recruitment followed by a prolonged exclusion. SAF-A recruitment corresponds to its binding to Poly(ADP-ribose) while its exclusion is dependent on the activity of ATM, ATR and DNA-PK and reflects the dissociation from chromatin of SAF-A associated with ongoing transcription. Having established that SAF-A RNA-binding domain recapitulates SAF-A dynamics, we show that this domain is part of a complex comprising several mRNA biogenesis proteins of which at least two, FUS/TLS and TAFII68/TAF15, exhibit similar biphasic dynamics at sites of damage. Using an original reporter for live imaging of DNA:RNA hybrids (R-loops), we show a transient transcription-dependent accumulation of R-loops at sites of DNA damage that is prolonged upon inhibition of RNA biogenesis factors exclusion. We propose that a new component of the DDR is an active anti-R-loop mechanism operating at damaged transcribed sites which includes the exclusion of mRNA biogenesis factors such as SAF-A, FUS and TAF15.